2010
DOI: 10.1037/a0019369
|View full text |Cite
|
Sign up to set email alerts
|

Capuchins (Cebus apella) can solve a means-end problem.

Abstract: Three capuchin monkeys (Cebus apella) were tested on a 2-choice discrimination task designed to examine their knowledge of support, modeled after Hauser, Kralik, and Botto-Mahan's (1999) experiments with tamarins. This task involved a choice between 2 pieces of cloth, including 1 with a food reward placed on its surface, and a second cloth with the food reward next to its surface. After reliably solving the basic problem, the capuchins were tested with various alternations of the original food reward and cloth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
1
13
1
Order By: Relevance
“…The implications of the failures reported for Povinelli's chimpanzees (2000) are problematic, relative to findings with other captive nonhuman primates (e.g., Deblauwe et al, 2006;Fragaszy et al, 2004;Sakura and Matsuzawa, 1991;Tonooka et al, 1997;Westergaard et al, 1995;Yocom and Boysen, 2010), but especially given the demonstrated prowess of wild chimpanzees in extensive and creative use of objects as tools in their environment. Why would captive chimpanzees not exhibit knowledge of physical support when such capabilities are both advantageous and necessary for their survival in the wild?…”
mentioning
confidence: 81%
“…The implications of the failures reported for Povinelli's chimpanzees (2000) are problematic, relative to findings with other captive nonhuman primates (e.g., Deblauwe et al, 2006;Fragaszy et al, 2004;Sakura and Matsuzawa, 1991;Tonooka et al, 1997;Westergaard et al, 1995;Yocom and Boysen, 2010), but especially given the demonstrated prowess of wild chimpanzees in extensive and creative use of objects as tools in their environment. Why would captive chimpanzees not exhibit knowledge of physical support when such capabilities are both advantageous and necessary for their survival in the wild?…”
mentioning
confidence: 81%
“…In many respects, they are considered the “poor person’s chimpanzee” with cognitive skills closely in line with those shown by apes and Old World monkey species in a variety of tasks including, but not limited to, tests of quantity judgment, self control, tool use, concept formation, analogical reasoning, and spatial representations (Beran 2008; Beran et al 2008a, 2008b; D’Amato and Colombo 1988; Evans, Beran and Addessi 2010; Evans and Westergaard 2004; Flemming 2011; Judge, Evans and Vyas 2005; Kennedy and Fragaszy 2008; McGonigle, Chalmers and Dickinson 2003; Poti et al 2010; Wright and Katz 2006; Yocum and Boysen 2010). But, recent research has indicated that capuchin monkeys lack one capacity that both apes and Old World monkeys (and perhaps even other species) have been argued to possess: metacognition.…”
Section: Introductionmentioning
confidence: 90%
“…Piaget’s support problem (Piaget 1952) has been used in a variety of species to test for their understanding of means-end connections (e.g., great apes: Povinelli et al 2000; Herrmann et al 2008; monkeys: Hauser et al 1999; Yocom and Boysen 2010; Yamazaki et al 2011; elephants: Irie-Sugimoto et al 2008; and kea: Auersperg et al 2009). It involves a target object (usually a piece of food) that is placed out of reach of the subject on a support (e.g., a piece of cloth or a wooden board) that is within the subject’s reach.…”
Section: Introductionmentioning
confidence: 99%
“…In the classic setup, the subjects are presented with two choices: a support that carries a piece of reward, and a second support beside which another piece of reward has been placed. Subjects may solve this task spontaneously (e.g., Povinelli et al 2000; Herrmann et al 2008; Auersperg et al 2009; Yamazaki et al 2011) or learn to solve it after a number of sessions (e.g., Hauser et al 1999; Irie-Sugimoto et al 2008; Yocom and Boysen 2010). In either case, however, it remains unclear whether the subjects understood the causal structure of the task, or whether they solved the task based on perceptual cues such as contact between reward and support or perceptual containment of the reward within the support.…”
Section: Introductionmentioning
confidence: 99%